The Gospel according to Mark as Episodic Narrative - Breytenbach, Cilliers (Novum Testamentum, Supplements, 2021)
In this collection of thematically arranged essays on the Gospel according to Mark, the first part highlights its reception in early Christianity, its text form as an episodic narrative and its relation to contemporary genres. It recognizes Mark's dependence on traditions from and about Jesus of Nazareth and the presupposed knowledge about the narrated locations in Galilee. The second part focuses on the discourse itself, presenting studies on style, use of metaphor, intertextuality, and strategies of persuasion. The third part treats the Christology, ethics and eschatology and the way in which the narrator gives meaning to Jesus's death. The fourth part returns to the burning issue of what lies behind Mark and how we can study it, ending with a proposal to discuss the composition of the narrative within the framework of performance theory.